2017
DOI: 10.1007/164_2017_7
|View full text |Cite
|
Sign up to set email alerts
|

Delta Opioid Receptor and Peptide: A Dynamic Therapy for Stroke and Other Neurological Disorders

Abstract: Research of the opioid system and its composite receptors and ligands has revealed its promise as a potential therapy for neurodegenerative diseases such as stroke and Parkinson's Disease. In particular, delta opioid receptors (DORs) have been elucidated as a therapeutically distinguished subset of opioid receptors and a compelling target for novel intervention techniques. Research is progressively shedding light on the underlying mechanism of DORs and has revealed two mechanisms of DOR neuroprotection; DORs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…The damaging events in global ischemic injury include acute injury (such as excitotoxicity and free radical injury) and prolonged damage (such as edema and inflammation), eventually leading to neuronal death after days of ischemia 3 . DADLE, a DOR agonist, has been proven to have therapeutic effects in stroke and many other neurological disorders including epilepsy, spinal cord injury, and neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease, with poorly understood mechanisms 25 . In this study, we showed that DADLE-induced DOR activation promoted CA1 neuronal survival and astrocytic activation on day 7 post-ischemia ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The damaging events in global ischemic injury include acute injury (such as excitotoxicity and free radical injury) and prolonged damage (such as edema and inflammation), eventually leading to neuronal death after days of ischemia 3 . DADLE, a DOR agonist, has been proven to have therapeutic effects in stroke and many other neurological disorders including epilepsy, spinal cord injury, and neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease, with poorly understood mechanisms 25 . In this study, we showed that DADLE-induced DOR activation promoted CA1 neuronal survival and astrocytic activation on day 7 post-ischemia ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Front and center have been the ability of δOR selective agonists to reduce chronic pain, be it inflammatory, neuropathic, or migraine [ 7 ]. δOR agonists have shown promise in preventing cardiac and cerebral ischemia [ 8 ], as a potential treatment for neurodegenerative diseases [ 9 , 10 , 11 , 12 , 13 ], and both δOR agonists and antagonists have been proposed as mechanisms for the treatment of alcohol use disorder [ 5 , 14 , 15 , 16 ]. Outside the central nervous system, δOR antagonism and positive allosteric modulation of δOR has been proposed as a treatment for gastrointestinal motility disorders, such as irritable bowel syndrome [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The δ-opioid receptor (δOR) is a G-protein coupled receptor (GPCR) within the opioid family that has been considered as therapeutic target for the treatment of migraine, chronic pain, anxiety, and major depressive disorder ( Jutkiewicz, 2006 ; Perrine et al, 2006 ; Pradhan et al, 2011 ; Pradhan et al, 2014 ; Gendron et al, 2016 ; Cahill et al, 2022 ). δOR agonists have also been proposed as promising treatments for alcohol use disorder, ischemia, and stroke ( Schultz et al, 1997 ; Karck et al, 2001 ; Alongkronrusmee et al, 2018 ; Grant Liska et al, 2018 ; Sheng et al, 2018 ); particularly as δOR agonists generally display negligible abuse potential ( Van Rijn et al, 2012 ; Hudzik et al, 2014 ; Conibear et al, 2020 ; Gutridge et al, 2021 ) and thus, would be safer alternatives relative to µ-opioid receptor drugs. Yet, in contrast to the µ-opioid and κ-opioid receptor, no δOR selective compounds have been approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%